Oxidative Stress in Cardiovascular Inflammation: Its Involvement in Autoimmune Responses - Elisabetta Profumo; Brigitta Buttari; Rachele Riganò (International Journal of Inflammation)
Recently, it has become clear that atherosclerosis is a chronic inflammatory disease in which inflammation and immune responses play a key role. Accelerated atherosclerosis has been reported in patients with autoimmune diseases, suggesting an involvement of autoimmune mechanisms in atherogenesis. Different self-antigens or modified self-molecules have been identified as target of humoral and cellular immune responses in patients with atherosclerotic disease. Oxidative stress, increasingly reported in these patients, is the major event causing structural modification of proteins with consequent appearance of neoepitopes. Self-molecules modified by oxidative events can become targets of autoimmune reactions, thus sustaining the inflammatory mechanisms involved in endothelial dysfunction and plaque development. In this paper, we will summarize the best characterized autoantigens in atherosclerosis and their possible role in cardiovascular inflammation.